VALIDASI METODE PENETAPAN KADAR GABAPENTIN TERDERIVATISASI SECARA HIGH PERFORMANCE LIQUID CHROMATOGRAPHY DAN APLIKASINYA DALAM SEDIAAN KAPSUL - Nurmaya Effendi (As-Syifaa Jurnal Farmasi, 2011)
Gabapentine, is a new antiepileptic drug which has a structural analogue of neurotransmitter γ-aminobutyric acid (GABA). Gabapentine inhibits calcium uptake of gated calcium channels presinaps in the brain. This research aimed to develop and validate a new HPLC method with UV detection for determination of gabapentine in capsule. The method is based on the reaction of gabapentine with 1-fluoro-2,4-dinitrobenzen (FDNB) in acetonitrile which carried out in the presence of borate buffer (pH = 9,5) at 65oC for 20 minutes, which formed a yellow colored product with the absorption at 367 nm. The product was separated by HPLC using A Zorbax ODS (Agilent) column (250 x 4.6 mm, 5 µm) was utilized as stationary phase and 50 mM acetate buffer (pH 3.7) : methanol : acetonitril (25 : 30 : 45 v/v/v) as mobile phase, with flow rate 0.8 mL/min, and the detection at 367 nm.The purposed method was validated by means of accuracy, precision, linearity, selectivity, LOD and LOQ, and the complied with the requirement for validity. The method has been succesfully applied for the determination of gabapentine in capsule with LOD = 1.05 µg/mL and LOQ = 3.49, linear quantitative response curve was generated over a concentration range of 3.49 - 100 µg/mL with the correlation coefficient of 0.99996 and recovery range of 97.27 – 104.24% with RSD 2.63%.Keywords : gabapentin, FDNB, HPLC, validation